A comparison of soil Staphylococcus aureus and fecal indicator bacteria concentrations across land uses in a Hawaiian watershed. Issue 5 (14th July 2022) - Gerken, Tyler; Wiegner, Tracy N.; Economy, Louise M.
Abstract: Staphylococcus aureus, methicillin‐resistant S. aureus (MRSA), and fecal indicator bacteria (FIB; Enterococcus spp., Clostridium perfringens ) concentrations increase in Hawaiian streams and estuaries following storms and pose a health threat to recreational water users. To reduce this risk, watershed bacteria sources need to be identified for management actions. This study's goals were to identify soil bacteria sources among different land uses and to determine if their concentrations were associated with different soil properties. Soil samples were collected three times on 24 d between October 2017 and November 2018 at urban, agriculture, and native‐forest land uses in the Hilo Bay watershed, Hawaiʻi Island, Hawaiʻi. Soil bacteria concentrations were quantified using culturing techniques with selective media. Staphylococcus aureus, MRSA, and FIB were present in soil from all land uses. Bacteria concentrations were highest in urban soils and lowest in native‐forest soils, with up to three orders of magnitude differences among land uses. Staphylococcus aureus, MRSA, and FIB soil concentrations were positively correlated with each other and with soil temperature and pH, but inversely correlated with soil moisture and organic matter content. Our results demonstrate that soils are a watershed bacteria source and that some soil properties affect their concentrations. Identifying these sources is critical for implementing management actions to reduce pathogen loads to estuaries and transmission to recreational water users. Core Ideas: Staphylococcus aureus, methicillin‐resistant S. aureus (MRSA), and fecal indicator bacteria (FIB) were present in urban, agriculture, and native‐forest soils. S. aureus, MRSA, and Enterococcus spp. concentrations were highest in urban soils and lowest in native‐forest soils. Enterococcus spp. concentrations varied by land use; C. perfringens did not. S. aureus, MRSA, and FIB soil concentrations were associated with one another. Soil properties were associated with soil S. aureus, MRSA, and FIB concentrations